Предмет: Алгебра, автор: 12freshik12

помогите пожалуйста срочно.

Приложения:

Ответы

Автор ответа: dukefissura
0

Ответ:

2a+(2b+a) = 2a+2b+a = 3a+2b\\ 8b-(2b+1) = 8b-2b-1=6b-1\\ 7n-(8n-2)=7n-8n+2=-n+2\\ -(2b+4)-(3b-1)=-2b-4-3b+1=-5b-3\\ (6x^{2} +5x^{4})-(3x^{2} -3x^{4} = 6x^{2} +5x^{4}-3x^{2} +3x^{4}=3x^{2} +8x^{4}  \\   (7k^{9}-5k^{3})-(5k^{9}+7k^{3}) =-7k^{9}+5k^{3}-5k^{9}-7k^{3} = -12k^{9} -2k^{3}\\ 3a+(5a+6b)-(2b+4a)-9a=3a+5a+6b-2b-4a-9a=-5a+4b\\ 7t^{3}-2+(3t^{3}-4t)-2t+(7-5k^{3}) = 7t^{3}-2+3t^{3}-4t-2t+7-5k^{3} = 10t^{3}+5-6t-5k^{3}  \\ (2a-1)+3b-4+(2b-1)+7a-2 = 2a-1+3b-4+2b-1+7a-2= 9a-8+5b   \\ \\

6x(2-3x)-4,5x(1-4x)-6,5x+2=9\\ 12x-18x^{2} -4,5x+18x^{2} -6,5x+2=9\\ x+2=9\\ x=9-2\\ x=7\    \\ otvet:x=7

Похожие вопросы
Предмет: Математика, автор: 6287780